2014 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--19939
|View full text |Cite
|
Sign up to set email alerts
|

A First-Year Course Based on Conceptual Design

Abstract: The College of Engineering at the University of Utah includes many majors and departments. A great deal of effort has been placed on helping students choose a major prior to enrolling at the institution, but many students still enroll as undecided students. A course was designed to provide an engineering design experience to undecided students as well as students who are not academically prepared. The objectives of the course are to help students select a major in engineering, and to provide an early design ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This latter characteristic makes it particularly challenging to incorporate authentic design challenges into first year coursework. As a result, some have sought shorter-term conceptual design projects [18,19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This latter characteristic makes it particularly challenging to incorporate authentic design challenges into first year coursework. As a result, some have sought shorter-term conceptual design projects [18,19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, the department's senior design instructors suggested that their students often lacked presentation skills and demonstrated poor technical writing. The researchers believed that they could start to address these issues in the aerospace engineering program's first-year class, as first-year engineering education has proven critical to student performance and retention [4,5]. Changes to this course were implemented starting in 2015.…”
Section: Introductionmentioning
confidence: 99%